2018
DOI: 10.15517/rbt.v66i2.33401
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of zooplankton community structure in Colombian Caribbean waters during two seasons

Abstract: Zooplankton is an important component to understand oceanographic dynamics, they are considered good indicators of environmental variability, since most species are short-lived they can be tight coupling of climate and population dynamics, and some taxa are sensitive to variables such as temperature, quality and quantity of food, oxygenation and stratification. In the Colombian Caribbean two oceanographic cruises were carried out, in order to characterize and analyze the biodiversity of the continental margin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…4). The is mainly because the upstream areas are vulnerable to hydrological disturbances and anthropogenic activities, which generally lead to a steeper NBSS slope (Dickerson et al 2010;Ma et al 2014;Medellin-Mora et al 2018). Comparing to García-Comas et al (2014), we found that the zooplankton size diversity in the Xiangxi Bay (mean value is 2.25) is slightly higher than that (mean value is 1.57) in the East China Sea.…”
Section: Discussionmentioning
confidence: 99%
“…4). The is mainly because the upstream areas are vulnerable to hydrological disturbances and anthropogenic activities, which generally lead to a steeper NBSS slope (Dickerson et al 2010;Ma et al 2014;Medellin-Mora et al 2018). Comparing to García-Comas et al (2014), we found that the zooplankton size diversity in the Xiangxi Bay (mean value is 2.25) is slightly higher than that (mean value is 1.57) in the East China Sea.…”
Section: Discussionmentioning
confidence: 99%
“…We found low salinity values in surface waters of the central zone, showing the influence of waters of the Magdalena River in the oceanic zone, as well as sectors of high stratification. Low dissolved oxygen was recorded in this zone; values were lower at the surface (4 mg l −1 ) compared with other studies in oceanic waters of the Colombian Caribbean during the same period, which found values of 6–7 mg l −1 (Lozano-Duque et al ., 2010; Medellín-Mora et al ., 2018). A recent study reported values of 4.2 mg l −1 in the river, 6.9 mg l −1 in Bocas de Ceniza and 7.0 mg l −1 in the adjacent ocean (8 km from the mouth of river at 100 m depth) (Torregroza-Espinosa et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The north-east oceanic stations showed low BVF (less stratification) and the deepest MLD in comparison to the central and south-west zones; these results agree with values previously recorded for the study period during the rainy season (Medellín-Mora et al ., 2018; Montoya-Sánchez et al ., 2018; Correa-Ramírez et al ., 2020) and are consistent with high values of geostrophic currents and deeper mixing layer in the offshore waters of the northern Colombian Caribbean Sea (Supplementary Figure S5). In the Caribbean Sea off Colombia the stratification (BVF) is dominated by salinity, which makes the water column highly stable to the depth of the subsurface salinity maximum (100–200 m), and mechanical mixing is the dominant process of salt diffusion from the SUW towards the surface (Correa-Ramírez et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations